Principles of management - I (BMS first year, 1st semester) - Kale N.G., Ahmed M. (Vipul prakashan,Mumbai, 2008)
B.M.S.
ENGLISH
Keywords: Principles of management - I (BMS first year, 1st semester); B.M.S.; B.M.S.